2017
DOI: 10.14348/molcells.2017.2236
|View full text |Cite
|
Sign up to set email alerts
|

PKCθ-Mediated PDK1 Phosphorylation Enhances T Cell Activation by Increasing PDK1 Stability

Abstract: PDK1 is essential for T cell receptor (TCR)-mediated activation of NF-κB, and PDK1-induced phosphorylation of PKCθ is important for TCR-induced NF-κB activation. However, inverse regulation of PDK1 by PKCθ during T cell activation has not been investigated. In this study, we found that PKCθ is involved in human PDK1 phosphorylation and that its kinase activity is crucial for human PDK1 phosphorylation. Mass spectrometry analysis of wild-type PKCθ or of kinase-inactive form of PKCθ revealed that PKCθ induced ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…9 Phosphoinositide-dependent protein kinase-1 (PDK1) is a member of the atypical glandular cell AGC kinase subfamily that regulates the activities of most atypical glandular cell kinases during different development stages and treatment of cancers. 14,15 PDK1 is proved to be a potential therapeutic target against angiosarcoma cells and is required in the leucine-induced stimulation of the cardiac mammalian target of rapamycin (mTOR)/p70 ribosomal S6 kinase (p70S6K) pathway. 16,17 Currently, it is widely reported that phosphatidylinositol 3-kinase (PI3K)/Akt/mTOR signaling pathway acts as an essential pathway in the regulation of cell autophagy and apoptosis.…”
mentioning
confidence: 99%
“…9 Phosphoinositide-dependent protein kinase-1 (PDK1) is a member of the atypical glandular cell AGC kinase subfamily that regulates the activities of most atypical glandular cell kinases during different development stages and treatment of cancers. 14,15 PDK1 is proved to be a potential therapeutic target against angiosarcoma cells and is required in the leucine-induced stimulation of the cardiac mammalian target of rapamycin (mTOR)/p70 ribosomal S6 kinase (p70S6K) pathway. 16,17 Currently, it is widely reported that phosphatidylinositol 3-kinase (PI3K)/Akt/mTOR signaling pathway acts as an essential pathway in the regulation of cell autophagy and apoptosis.…”
mentioning
confidence: 99%
“…PDK1 is required for TCR-mediated activation of NF-κB and PKCθ; selective deletion of PDK1 in T cells abrogates activation of NF-κB and PKCθ 98 . Recently, it was shown that PKCθ induces phosphorylation of PDK1 100 , resulting in T cell activation and TCR-induced NF-κB activation [96][97][98][100][101][102] . PKCθ is involved in the activation of NF-κB 103 .…”
Section: The Pkcθ-ikk-nf-κb Pathwaymentioning
confidence: 99%
“…This kinase is indispensable for T lymphocyte activation. 44,45 Cell-type specific PDK1 deletion revealed that the absence of PDK1 leads to stunted development of all lymphocytes, including T cells, B cells or NK cells. Therefore, targeting PDK1 very likely causes significant side effects from an immune perspective.…”
Section: Introductionmentioning
confidence: 99%